Current practice of Rapid Sequence Induction (RSI) in pediatric anesthesia: A survey from India - Sana Yasmin Hussain; Pratibha Panjiar; Dhruv Jain; Samiksha Khanooja (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Rapid Sequence Induction (RSI) is an established technique to secure the airway in patients who are at risk of aspiration. The practice of RSI in the pediatric population is highly variable due to numerous patient factors. We conducted a survey to find the prevalent practices and adherence of anesthesiologists to the practice of RSI in different pediatric age groups and whether it differs with the experience of the anesthesiologist or the age of the child. Material and Methods: The survey was conducted among residents and consultants attending the pediatric national anesthesia conference. The questionnaire consisted of 17 questions on anesthesiologist's experience, adherence, conduct of pediatric RSI, and the reason for nonadherence. Results: The response rate was 75% (192/256). Anesthetists having less than 10 years of experience adhered to RSI more often as compared to respondents with more experience. Succinylcholine was the most commonly used muscle relaxant for induction, with use increasing in higher age groups. The application of cricoid pressure increased with increasing age groups. Anesthetists with >10 years of experience used cricoid pressure more often in age groups of <1 year (P < 0.05). In a scenario of intestinal obstruction, adherence to RSI was low in pediatrics as compared to adults, with 82% of respondents agreeing to this. Conclusion: This survey on the practice of RSI in the pediatric population demonstrates wide variation in the practice among individuals and the reasons for nonadherence as compared to adults. It highlights the need felt by almost all the participants for more research and protocol in the practice of pediatric RSI.